2017
DOI: 10.1371/journal.pgen.1006678
|View full text |Cite
|
Sign up to set email alerts
|

Rare variants in fox-1 homolog A (RBFOX1) are associated with lower blood pressure

Abstract: Many large genome-wide association studies (GWAS) have identified common blood pressure (BP) variants. However, most of the identified BP variants do not overlap with the linkage evidence observed from family studies. We thus hypothesize that multiple rare variants contribute to the observed linkage evidence. We performed linkage analysis using 517 individuals in 130 European families from the Cleveland Family Study (CFS) who have been genotyped on the Illumina OmniExpress Exome array. The largest linkage peak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 61 publications
(54 reference statements)
1
30
0
Order By: Relevance
“…Consistent with this evidence, to date, variants in Mendelian HTN syndromes, do not explain the variance of BP in the general population. Although linkage studies are often considered to have low statistical power, many disease variants have been identified through linkage analysis, such as the BRCA1 and BRCA2 genes for breast cancer and RBFOX1 for BP [48,49]. We used LOD score > 3, the initial proposal by Morton [25], as our genome-wide significance level corresponding to a principled posterior probability of linkage of 95 percent (Ott 1991 [26], p.66).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with this evidence, to date, variants in Mendelian HTN syndromes, do not explain the variance of BP in the general population. Although linkage studies are often considered to have low statistical power, many disease variants have been identified through linkage analysis, such as the BRCA1 and BRCA2 genes for breast cancer and RBFOX1 for BP [48,49]. We used LOD score > 3, the initial proposal by Morton [25], as our genome-wide significance level corresponding to a principled posterior probability of linkage of 95 percent (Ott 1991 [26], p.66).…”
Section: Discussionmentioning
confidence: 99%
“…Rbfox1 (RNA-binding protein fox-1) is the associated gene of lncRNA 1700123O21Rik. He et al identified that rare, exonic variants in Rbfox1 had protective effects on BP traits, which could be important in searching new drugs for cardiovascular disease [ 26 ]. Hence, Rbfox1 is expressed in multiple tissues that may relate to blood pressure, and the identification of these rare coding variants will facilitate precision medicine in treating cardiovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…4,5,6 For example, Igartua et al 7 identified two novel rare variants associated with low-density lipoprotein cholesterol and high-density lipoprotein cholesterol with larger effects than the previously discovered variants within the known blood lipid associated loci. In another study by He et al, 8 multiple rare variants were found to be associated with lower systolic blood pressure. Successes from rare variant association studies highlight the importance of rare variants to complex disease susceptibility.…”
Section: Introductionmentioning
confidence: 91%